Polskie kino w zwierciadle francuskich archiwów audiowizualnych INA: między obrazem narodowym a estetyką polityczną - Głębicka-Giza, Barbara (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2025)
This text is the result of archival research conducted at the Institut national de l’audiovisuel (INA) in Paris. An analysis of the INA archives from the perspective of a Polish film scholar facilitates not only a mapping of the media presence of Polish cinema in French television and radio between 1945 and 1989 but also critical reflections on how an external observer – as represented by the French media – constructed an image of Polish culture, identity, and history. This perspective is particularly significant in the context of a state and a national cinema that operated for decades under conditions of political dependency, restricted access to free markets, and censorship. Research conducted within INA’s archival databases allows for the reconstruction of the evolving French perception of Polish cinema during this period. Moreover, it sheds new light on the function of film as a medium of social communication and as a tool of political semiotics. In this sense, INA emerges not only as a repository of audiovisual resources but also as a mirror reflecting the shifting image of Poland and Polish cinema within the Western media discourse. The text also provides numerous previously unexplored insights for Polish film scholars, particularly regarding Polish filmmakers and their appearances in the French media landscape.